2020
DOI: 10.1089/pmr.2020.0055
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-Reported Quality Measures and Their Correlates in Home Hospice Care

Abstract: Background: A majority of hospice care is delivered at home, with significant caregiver involvement. Identifying factors associated with caregiver-reported quality measures could help improve hospice care in the United States. Objectives: To identify correlates of caregiver-reported quality measures: burden, satisfaction, and quality of end-of-life (EoL) care in home hospice care. Design: A cross-sectional study was conducted from April 2017 through February 2018. Setting/Subjects: A nonprofit, urban hospice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Compared with the families of middle-aged and elderly late-stage cancer patients, youth family members have a higher awareness of hospice care and a greater attitude of acceptance and compliance. Phongtankuel et al [ 13 ] reported a significantly negative correlation between the quality of life of family caregivers and the age of caregivers for end-of-life care patients. Hospice care is a humane and scientific care plan provided to patients with advanced cancer, which can alleviate patients’ cancer pain and physical discomfort, improve their quality of life, enable them to accept death with dignity and peace and spend a meaningful remaining life[ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the families of middle-aged and elderly late-stage cancer patients, youth family members have a higher awareness of hospice care and a greater attitude of acceptance and compliance. Phongtankuel et al [ 13 ] reported a significantly negative correlation between the quality of life of family caregivers and the age of caregivers for end-of-life care patients. Hospice care is a humane and scientific care plan provided to patients with advanced cancer, which can alleviate patients’ cancer pain and physical discomfort, improve their quality of life, enable them to accept death with dignity and peace and spend a meaningful remaining life[ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phongtankuel et al 41 found that lower levels of comfort with managing patient symptoms among caregivers were associated with lower satisfaction scores among family members of hospice patients. Rhodes et al 42 found that providing the "right" amount of medication and help, as perceived by family members of hospice patients, along with other aspects of appropriate information provision (again as perceived by family members), were associated with "excellent" care ratings among family members of hospice patients.…”
Section: Predictors Of Hospice Satisfaction: Communication Comfort An...mentioning
confidence: 99%
“…Main Relevant Findings Moore et al (2020) 36 34.5% of patients/family/caregivers strongly agree with "Overall I am satisfied with this telehealth system" 40.5% of patients/family/caregivers agree with "Overall I am satisfied with this telehealth system" Munn et al (2006) 37 95% of family members "very satisfied" with care if patient was enrolled in hospice 99% of family members "very satisfied" with care if patient was not enrolled in hospice Oliver et al (2013) 38 Mean overall satisfaction with pain management score was 9.0 e Mean satisfaction with pain management score was 8.4 among subsample that specifically discussed pain concerns e Ong et al (2016) 39 Family members of patients who received general inpatient care were more satisfied than those who received routine home care; 88% vs 73%, respectively, rated care as excellent Being kept informed about the patient's condition is associated with higher odds of satisfaction in home and inpatient care Being provided with adequate information about what to expect when patient was dying is associated with higher odds of satisfaction in inpatient care Sufficient discussion with hospice team members concerning family members' religious or spiritual beliefs is associated with higher odds of satisfaction in home care Being provided with the correct amount of emotional support after the patient's death is associated with higher odds of satisfaction in home care Parast et al (2018) 40 Payer for hospice care: Medicaid only or Medicaid and private insurance are negatively associated with overall rating of hospice Payer for hospice care: Both Medicare and Medicaid are negatively associated with overall rating of hospice Phongtankuel et al (2020) 41 Hospice discharge to hospital associated with lower satisfaction scores Hospice discharge due to death associated with lower satisfaction scores Caregiver with greater than high school education associated with lower satisfaction scores Caregiver less comfortable managing symptoms associated with lower satisfaction scores Rhodes et al (2008) 42 Adequate contact with hospice about family member's religious and spiritual beliefs positively associated with "excellent" care rating "Right amount" of emotional support provided to family prior to patient death positively associated with "excellent" care rating "Right amount" of emotional support provided to family after patient death positively associated with "excellent" care rating Hospice team always kept family informed about patient's condition positively associated with "excellent" care rating Adequate information about what to expect while patient was dying positively associated with "excellent" care rating Receiving information from hospice team about medications used to manage patient's pain positively associated with "excellent" care rating Not wanting more information than was received about medications used to manage patient's pain positively associated with "excellent" care rating Not wanting more information than was received about medications used to manage patient's trouble breathing positively associated with "excellent" care rating Not wanting more information than was received about what was being done for patient's trouble breathing positively associated with "excellent" care rating Hospice team never gave confusing or contradictory information about the patient's medical treatment positively associated with "excellent" care rating Always 1 nurse identified as in charge of patient's care positively associated with "excellent" care rating No problems with hospice doctors...…”
Section: Main Relevant Findingsmentioning
confidence: 99%
“…Achieving this level of integration will also require that health care organizations recognize and emphasize the relationship between caregiver integration and quality of care. Identifying the related structure, process, or outcome quality measures will require further study, and policymakers will need to develop procedures for reimbursing high performing clinicians and health care systems (i.e., specifically in terms of their engagement with caregivers) (National Alliance for Caregiving, 2021; Phongtankuel et al, 2020). This will also require institutional encouragement of greater collaboration between physicians and other professionals such as social workers, medical interpret-ers, patient navigators, and community health workers, all of whom could facilitate important discussions with caregivers and contribute to the building of trust between systems, providers, caregivers, and patients.…”
Section: Implications For Policy and Practicementioning
confidence: 99%